Personal Perspectives on Plant Ribosomal RNA Genes Research: From Precursor-rRNA to Molecular Evolution - Hemleben, Vera; Grierson, Donald; Borisjuk, Nikolai; Volkov, Roman A.; Kovarik, Ales (Frontiers in Plant Science, 2021)
The history of rDNA research started almost 90 years ago when the geneticist, Barbara McClintock observed that in interphase nuclei of maize the nucleolus was formed in association with a specific region normally located near the end of a chromosome, which she called the nucleolar organizer region (NOR). Cytologists in the 20th century recognised the nucleolus as a common structure in all eukaryotic cells, using both light and electron microscopy and biochemical and genetic studies identified ribosomes as the subcellular sites of protein synthesis. In the mid to late 1960s the synthesis of nuclear-encoded rRNA was the only system in multicellular organisms where transcripts of known function could be isolated, and their synthesis and processing could be studied. Cytogenetic observations of NOR regions with altered structure in plant interspecific hybrids and detailed knowledge of structure and function of rDNA were prerequisites for studies of nucleolar dominance, epistatic interactions of rDNA loci and epigenetic silencing. In this article we focus on the early rDNA research in plants, performed mainly at the dawn of molecular biology in the 60 to 80-ties of the last century which presented a prequel to the modern genomic era. We discuss – from a personal view - the topics such as synthesis of rRNA precursor (35S pre-rRNA in plants), processing, and the organisation of 35S and 5S rDNA. Cloning and sequencing led to the observation that the transcribed and processed regions of the rRNA genes vary enormously, even between populations and species, in comparison with the more conserved regions coding for the mature rRNAs. Epigenetic phenomena and the impact of hybridisation and allopolyploidy on rDNA expression and homogenisation are discussed. This historical view of scientific progress and achievements sets the scene for the other articles highlighting the immense progress in rDNA research published in this special issue of Frontiers in Plant Science on “Molecular organization, evolution, and function of ribosomal DNA”.